A symbolic shortest path algorithm for computing subgame-perfect Nash equilibria - Góngora, Pedro A.; Rosenblueth, David A. (Zielona Góra: Uniwersytet Zielonogórski)
Consider games where players wish to minimize the cost to reach some state. A subgame-perfect Nash equilibrium can be regarded as a collection of optimal paths on such games. Similarly, the well-known state-labeling algorithm used in model checking can be viewed as computing optimal paths on a Kripke structure, where each path has a minimum number of transitions.
Keywords: shortest path; Bellman-Ford; Nash equilibrium; BDD; model checking